Wake up and smell the coffee: Challenges and opportunities for better price transmission along the coffee value chain of El Salvador - Camilo, Karen; Charry, Andrés; Reyes, Byron A. (2022)
The Alliance Bioversity International-CIAT implemented a study in El Salvador, whose goal was to make more transparent the costs and value-added along the coffee value chain, as well as to identify gaps and limitations that cause small and medium-sized farmers to remain in poverty and food insecurity, to make recommendations for policy action to make the value chain more equitable and environmentally sustainable. This brief summarizes the results of this study.